Enhanced expression of p21 promotes sensitivity of melanoma cells towards targeted therapies. Issue 8 (2nd June 2022) - Fröhlich, Lisa Marie; Makino, Elena; Sinnberg, Tobias; Schittek, Birgit
Abstract: Metastatic melanoma patients benefit from the approved targeted BRAF inhibitor (BRAFi) therapy. Despite the great progress in the therapeutic approach to combat metastatic melanoma, fast emerging drug resistance in patients limits its long‐term efficacy. In this study, we aimed to unravel the role of the p53 target gene CDKN1A/p21 in the response of melanoma cells towards BRAFi. We show that p53 activation increases BRAFi sensitivity in a synergistic manner exclusively in cells with a high expression of CDKN1A/p21. In a similar way, high expression of p21 was associated with a better response towards the mouse double minute 2 inhibitor (MDM2i) compared to those with low p21 expression. Indeed, p21 knockdown decreased the sensitivity towards both targeted therapies. The results indicate that the sensitivity of melanoma cells towards targeted therapies (BRAFi and MDM2i) is dependent on the p21 protein level in the cells. In addition to that, we found that p53 negatively regulates p73 expression; however, p73 seems not to have an influence on p53 expression. These findings offer new potential strategies for the treatment improvement of melanoma patients with high basal p21 levels with BRAFi by increasing treatment efficacy using combination therapies with p53 activating substances, which are able to further increase p21 expression levels. Furthermore, the data suggest that the expression and induction level of p21 could be used as a predictive biomarker in melanoma patients to forecast the outcome of a treatment with p53 activating substances and BRAFi. All in all, this manuscript shows the distinct role of p53 family members and its impact on melanoma therapy. In future, individualized treatment regimens based on p21 basal and induction levels could help melanoma patients with limited treatment options.